Kajian Strukturalisme Puisi ‘Dompet Ayah, Sepatu Ibu’ Karya J.S. Khairen: Struktur Fisik dan Struktur Batin - Anwar, Anatasya Faradina; Nur'aini; Khaerani, Zarnita; Rozikin, Derry Vikry Khoirur; Warsiman (Balai Diklat Keagamaan Surabaya, 2025)
The development of the times has made literature not only a medium for creating works, but also a place for writers to express themselves, one of which is through poetry. This study aims to examine the poetry in the novel Dompet Ayah, Sepatu Ibu by J.S. Khairen to understand the meaning contained in it. This research uses a qualitative descriptive method. The approach used in this research is structuralism approach. The data collection techniques used are documentation study or commonly called document review, reading technique, and note-taking technique. This research analyzes the data by observing and examining the inner elements and physical elements in the poems contained in the novel Dompet Ayah, Sepatu Ibu by J.S. Khairen. Based on the research conducted, the results obtained in the form of the physical structure of poetry which includes the form of poetry, diction, concrete words, language style, and imagery, and obtained the inner structure of poetry which includes theme, tone, atmosphere and mandate.